Ukrainian Teachers’ Capacity to Teach Online Under Quarantine and Martial Law - Kolomiiets, Alla; Gromov, Ievgen; Zhovnych, Olesia; Ihnatova, Olena; Kolomiiets, Dmytro; Babchuk, Yurly; Ivanichkina, Natalia (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2024)
The article analyzes the capacity of Ukrainian pedagogical university faculty and students to teach remotely under unstable conditions like quarantine and martial law. Issues associated with their self-directed preparation to teach online under these conditions are also discussed. The study involved 594 students at Vinnytsia State Pedagogical University (420 bachelor program students and 174 master program students), 387 faculty members (206 social sciences and liberal arts teachers, 181 natural sciences teachers), and forty-five experts (twenty-five university leaders and twenty regional stakeholders). To determine the level of skills and abilities of the pedagogical university students, the authors monitored their educational progress in fundamental, professional, and didactical disciplines beginning in June 2020 when the first wave of the COVID-19 pandemic started, until June 2023 when there was a partial adaptation of teachers and students to online teaching in emergency situations. Included in this period was the point at which Russia’s invasion of Ukraine peaked in intensity, June 2022. The authors propose organizational and methodological activities to help improve the skills that pedagogical university teachers and students need for online teaching under quarantine and martial law. The effectiveness of the applied experimental methods was determined by analytical reports of all faculties regarding the quality of the acquired knowledge. Statistical analysis was used to determine the results of expert evaluation.